2021
DOI: 10.1371/journal.pone.0259499
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence applications in social media for depression screening: A systematic review protocol for content validity processes

Abstract: Background The popularization of social media has led to the coalescing of user groups around mental health conditions; in particular, depression. Social media offers a rich environment for contextualizing and predicting users’ self-reported burden of depression. Modern artificial intelligence (AI) methods are commonly employed in analyzing user-generated sentiment on social media. In the forthcoming systematic review, we will examine the content validity of these computer-based health surveillance models with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Jacobson and Gruzd (2020) posit that social media screening has introduced new forms of discrimination, such as evaluating a candidate's influence based on the size of their social network and using photo scanners to predict the mental well-being of a candidate. Algorithms have been designed to predict with high accuracy whether someone is suffering from a mental disorder such as depression, suicide ideation, and schizophrenia (Chancellor et al, 2019;Owusu et al, 2021). Such advanced algorithms can be used to evaluate mental health based on image characteristics such as colorfulness, sharpness, naturalness, and facial presentation (Owusu et al, 2021).…”
Section: Implications For Adverse Impact and Protected Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacobson and Gruzd (2020) posit that social media screening has introduced new forms of discrimination, such as evaluating a candidate's influence based on the size of their social network and using photo scanners to predict the mental well-being of a candidate. Algorithms have been designed to predict with high accuracy whether someone is suffering from a mental disorder such as depression, suicide ideation, and schizophrenia (Chancellor et al, 2019;Owusu et al, 2021). Such advanced algorithms can be used to evaluate mental health based on image characteristics such as colorfulness, sharpness, naturalness, and facial presentation (Owusu et al, 2021).…”
Section: Implications For Adverse Impact and Protected Groupsmentioning
confidence: 99%
“…Algorithms have been designed to predict with high accuracy whether someone is suffering from a mental disorder such as depression, suicide ideation, and schizophrenia (Chancellor et al, 2019;Owusu et al, 2021). Such advanced algorithms can be used to evaluate mental health based on image characteristics such as colorfulness, sharpness, naturalness, and facial presentation (Owusu et al, 2021). Although these efforts are laudable because they drive public health efforts to understand and design interventions for mental health disorders, the use of such algorithms in using social media information to assess applicants could promote selection biases and Type I errors (concluding falsely that a candidate is mentally ill when they are not).…”
Section: Implications For Adverse Impact and Protected Groupsmentioning
confidence: 99%
“…Due to a lack of authentic social interaction and the fear of being judged, individuals with depressive disorder may use social media networking to express their thoughts and feelings with people similar to themselves ( 4 ). Social media platforms such as Twitter, Facebook, Reddit and Instagram offer a virtual community network where people of various demographic backgrounds share sentiments, exchange information, and provide mutual support for common conditions ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies from the literature have demonstrated that social media can be an important avenue for predicting depression ( 6 10 ). Surveillance of the online content and users’ posting activity has been proposed as a complementary or alternative precision tool for the early detection of depression markers ( 5 ). In most studies, research objects include posts and photographs shared on social media by users with depressive disorder ( 11 ), and the posts are the main object between them.…”
Section: Introductionmentioning
confidence: 99%